2015
DOI: 10.1088/0004-637x/812/2/118
|View full text |Cite
|
Sign up to set email alerts
|

X-Ray Emission From the Taffy (Vv254) Galaxies and Bridge

Abstract: We present the first X-ray observations of the Taffy galaxies (UGC 12914/5) with the Chandra observatory and detect soft X-ray emission in the region of the gas-rich, radio-continuum-emitting Taffy bridge. The results are compared to Herschel observations of dust and diffuse [C II] line-emitting gas. The diffuse component of the Taffy bridge has an X-ray luminosity of L X 0.5 8 keV, which accounts for 19% of the luminosity of the sum for the two galaxies. The total mass in hot gas is (0.8-1.3) × 10 8 M e , whi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
26
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 89 publications
(194 reference statements)
9
26
1
Order By: Relevance
“…These values are in good agreement with those of Appleton et al (2015) who estimated the SFR using several different methods.…”
Section: Star Formation In the Taffy Systemsupporting
confidence: 89%
See 1 more Smart Citation
“…These values are in good agreement with those of Appleton et al (2015) who estimated the SFR using several different methods.…”
Section: Star Formation In the Taffy Systemsupporting
confidence: 89%
“…It is possible that this emission is bridge material superimposed on the northern disk, as it shares similar properties to other material in the bridge. X-ray emission, which we suggested was shock-heated gas left over from the initial collision between the Taffy galaxies (Appleton et al 2015), also occupies this region of the northwest disk of UGC 12915 and the bridge. To compare the PACS spectra of the extracted regions with the Condon et al (1993) and CO data from BIMA CO(1-0) (Gao et al 2003), we obtained calibrated data cubes of both sets of observations and performed extractions over similar areas to those of Figure 1.…”
mentioning
confidence: 77%
“…Numerical models of such a head-on collision between two gas rich galaxies (e.g., Struck 1997) and a detailed model of the Taffy system (Vollmer et al 2012) provide strong support for the idea that the gas left behind in the center of mass frame of the collision would be highly turbulent, and that some would be strongly shock heated. Appleton et al (2015) detected faint extended soft X-ray emission, and several compact point X-ray sources in the bridge, the former being consistent with shock-heated gas that has not had time to completely cool since the collision occurred. Finally, Lisenfeld & Völk (2010) concluded that the radio emission in the bridge could be explained in terms of cosmic rays accelerated in magnetic fields compressed in shocks.…”
Section: Introductionmentioning
confidence: 68%
“…Soft X-ray emission was observed over the entire bridge with the Chandra telescope as described in Appleton et al (2015). Several individual X-ray sources were also detected, indicative of recent star formation.…”
mentioning
confidence: 92%